ปัญหาเกี่ยวกับที่มา อำนาจหน้าที่ สถานะ และจำนวนขององค์กรอิสระตามรัฐธรรมนูญ ตามรัฐธรรมนูญแห่งราชอาณาจักรไทย พุทธศักราช 2550 - สกรรจ์ ปิ่นทองคำ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
Independent organs under the Constitution are entities established to be in charge of checking the use of state power and enhancing such duty there of under the system of checks and balances among the executive, legislative and judiciary to be more proficient for the purpose of protecting people’s right which may be affected by the use of the state power. The Constitution of the Kingdom of Thailand, B.E. 2550 has stipulated the independent organs’ structures, powers and duties, status and number with the intention of providing security for independent principle of performing the duties. In addition, the status of independent organs under the Constitution is an constitutional organ where can proficiently check the use of state power and shall not be intervened by any political groups. However, on the basis of the results of this research, it can be concluded that the provisions of the Constitution of the Kingdom of Thailand, B.E. 2550 regarding those structures, powers and duties, status and number of the independent organs become legal problems on the independent organs under the Constitution such as a problem of absence of people connection of the source of such independent organs under the Constitution, a problem of the check of the use of state power by independent organs under the Constitution and a problem of the independent organs under the Constitution’s status being not the real constitutional organ. Therefore, the author would recommend solutions for such legal problems on sources, powers and duties, status and number of the independent organs under the Constitution that there shall be a procedure on recruitment and selection of office holders of the independent organs under the Constitution to be connected with people, the structures and powers and duties of the independent organs under Act legislative shall be stipulated, affecting no longer independent organs under the Constitution and such check of the use of power by the independent organs shall be proceeded by the Administrative Court in all aspects in order to be in accordance with the Rule of Law.